Perturbations in gut microbiota in autism spectrum disorder: a systematic review - Tao, Xiangkun; Li, Zhuocan; Wang, Dongfang; Pu, Juncai; Liu, Yiyun; Gui, Siwen; Zhong, Xiaogang; Yang, Dan; Zhou, Haipeng; Tao, Wei; Chen, Weiyi; Chen, Xiaopeng; et al. (Frontiers in Neuroscience, 2025)
BackgroundAutism spectrum disorder (ASD) is a neurological and developmental disorder commonly accompanied by gut dysbiosis and gastrointestinal symptoms. Accumulating evidence supports a crucial role of gut microbiota dysbiosis in the pathophysiological mechanisms of ASD. However, the alteration of gut microbiota shows high heterogeneity across different studies. This study aims to identify potential biomarkers in the gut microbiota of patients with ASD.MethodsWe conducted a comprehensive analysis by searching the PubMed, Web of Science, Cochrane Library, and Embase databases, for studies assessing the changes of gut microbial diversity and taxa in ASD patients and healthy controls using high-throughput sequencing. Vote counting analyses were performed to identify consistently altered gut microbes associated with ASD.ResultsSixty-four studies involving 189 differentially abundant gut microbial taxa were included. Our synthesis provided no strong evidence for a difference in α-diversity between ASD patients and healthy controls, while studies were relatively consistent in reporting differences in β-diversity. Among 189 taxa, we identified three significantly increased taxa in ASD patients: Eubacteriales, Klebsiella, and Clostridium. Additionally, there were enriched trends of Oscillospira, Dorea, and Collinsella, and depleted trends of Streptococcus, Akkermansia, Coprococcus, and Dialister. These findings suggest that the disrupted intestinal microecology and functional changes in ASD are characterized by an enrichment of pro-inflammatory genera, a reduction of specific probiotics, lactic acid-producing and utilizing bacteria, and an imbalance of anti-inflammatory butyrate-producing bacteria. Substantial heterogeneity across studies concerning demographics and methodologies was also observed.ConclusionThis systematic review contribute to a further understanding of the role of gut microbiota in ASD and support the development of microbiota-based diagnostic and therapeutic strategies for ASD.